The Effect of Liquidity, Profitability and Solvency on the Value of the Company(Study of Transportation Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2017-2021) - Andriany, Dessy; Putra, Yananto Mihadi; Siswanti, Indra; Cahaya, Yohanes Ferry (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2024)
This study aims to empirically prove the effect of financial ratios for transportation companies in Indonesia listed on the Indonesia Stock Exchange in the 2017-2021 period on company value. The ratios used in this study are Liquidity (CR), Profitability (ROA), and Solvency (DER). This study used a quantitative approach with sample selection using purposive sampling method. The data used is secondary data and the data analysis used is statistical analysis in the form of multiple linear regression tests with SPSS 23.The results of this study show that partially, the variables of Liquidity (CR), Profitability (ROA), and Solvency (DER) have a positive and significant effect on Company Value measured using Price Book Value (PBV) in companies listed on the Indonesia Stock Exchange (IDX).